2019
DOI: 10.1186/s12935-019-0812-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Large tumor suppressor kinase 2 overexpression attenuates 5-FU-resistance in colorectal cancer via activating the JNK-MIEF1-mitochondrial division pathway

Abstract: Background 5-Fluorouracil (5-FU) is a standard treatment for colorectal cancer, but most patients develop 5-FU resistance. Here, we conducted experiments to identify an effective approach to augment 5-FU-based treatment in colorectal cancer in vitro. Methods SW480 cells were in the present study and treated with 5-FU. Besides, LATS2 adenovirus vectors were infected into SW480 cells. Western blotting, immunofluorescence and ELISA were used to evaluate cell death and mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…Mitochondrial division is a mechanism that leads to the production of fragments with increased ROS levels. A recent study focused on SW480, a CRC cell line corresponding to an early stage of CRC, and showed that 5‐FU resistance was induced by a reduction of mitochondrial division in relation with decreased expression of both mitochondrial elongation factor 1 and the large tumor suppressor kinase 2 (LATS2)‐Hippo pathway 38 …”
Section: Cellular Functions Disrupted By 5‐fumentioning
confidence: 99%
“…Mitochondrial division is a mechanism that leads to the production of fragments with increased ROS levels. A recent study focused on SW480, a CRC cell line corresponding to an early stage of CRC, and showed that 5‐FU resistance was induced by a reduction of mitochondrial division in relation with decreased expression of both mitochondrial elongation factor 1 and the large tumor suppressor kinase 2 (LATS2)‐Hippo pathway 38 …”
Section: Cellular Functions Disrupted By 5‐fumentioning
confidence: 99%
“…Merlin re-expression in glioma cells confers 5-FU sensitivity, likely through downregulating cIAP1 and cIAP2 that inhibit caspase activity and apoptosis [ 96 ]. Overexpression of LATS2 in combination with 5-FU treatment elevates the expression mitochondrial elongation factor 1 (MIEF1) via c-Jun N-terminal kinase (JNK) pathway, thus amplifying fatal mitochondrial stress [ 89 ].…”
Section: Hippo Signaling Pathway-mediated Drug Resistancementioning
confidence: 99%
“…thymidylate synthase or dihydrofolate reductase) [15,16]. Due to the suboptimal response rate of the presently used drugs, development of novel anti-cancer strategies acting on the thymidylate synthesis route is of high significance [17]. The enzyme dUTPase is tightly connected to this pathway, as dUMP is the sole precursor of de novo deoxythymidine triphosphate (dTTP) biosynthesis [14].…”
Section: Introductionmentioning
confidence: 99%